2005
DOI: 10.1177/0148607105029004255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amino Acid Infusion on Human Postoperative Colon Protein Synthesis in Situ

Abstract: ABSTRACT. Background: Amino acids are an integral part of parenteral nutrition because of their anabolic action helping to conserve body protein after surgical stress. At the gastrointestinal tract, an adequate supply of amino acids may be particularly important because of the gut's high rate of protein turnover, cell division, and proliferation. However, no information is available about the effects of amino acids on human intestinal protein metabolism after surgery. Methods: Studies were performed in postabs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
4
0
2
Order By: Relevance
“…In some pathophysiologic conditions, protein turnover is altered and may contribute to intestinal or systemic diseases. Gut protein metabolism can be affected by nutritional state (3)(4)(5) or nutritional interventions (1,4,(6)(7)(8). Amino acids, as constituents of proteins and signaling molecules, have been extensively tested in vitro and in vivo, but results have appeared to be model and condition dependent (9).…”
Section: Introductionmentioning
confidence: 99%
“…In some pathophysiologic conditions, protein turnover is altered and may contribute to intestinal or systemic diseases. Gut protein metabolism can be affected by nutritional state (3)(4)(5) or nutritional interventions (1,4,(6)(7)(8). Amino acids, as constituents of proteins and signaling molecules, have been extensively tested in vitro and in vivo, but results have appeared to be model and condition dependent (9).…”
Section: Introductionmentioning
confidence: 99%
“…The response of splanchnic protein synthesis and breakdown during amino acid absorption is not known. Dietary protein consumption has been reported to stimulate,16 not affect17 or decrease18 GIT protein synthesis in human subjects. No studies have been published in which the response of liver protein metabolism to feeding has been determined in human subjects, but it was shown that liver protein synthesis in rats is not affected by feeding 19…”
Section: Introductionmentioning
confidence: 98%
“…Gut protein metabolism can be affected by nutritional states or by specific nutrient supplementation in the small intestinal and the colonic mucosa contributing to intestinal homeostasis. Indeed, feeding increased protein synthesis rate in small intestinal mucosa compared to fasted state in humans .…”
Section: Introductionmentioning
confidence: 99%